Implementation of Automated Electronic Payment Control System with the Use Of Wireless Technologies for Fare Tariffing in Public Transport - Ðž. Boiko, Y; Ðž. Korol, S; L.Khorolskiy, V; M. Kantemyrova, R; O. Vdovychenko, V (International Journal of Engineering and Technology, 2018)
Purpose of the study. Implementation of automated electronic payment control system with the use of wireless technologies while urban transportation.Methods: The article describes the main characteristic of automated electronic payment control system (AEPCS) and proposes the stages of its implementation at the transport enterprise in order to ensure full control over the transportation process and cost estimates.Results: The use of the proposed automated payment control system will provide transport companies with control over the rolling stock operation, the number of passengers using this system, and load capacity of routes which enable the most efficient operation of vehicles on the line. The proposed kind of control can be carried out directly through the transport companyâ€™s database. For passengers, this system is easy to use, because having only a mobile phone or a smart card it is easy to pay for travel and control the amount of travel expenses for a certain period of time. At present, the software is in the final stage of testing and has positive results of the tests conducted.Â Â